CTAB Method to Isolate DNA from Silica-Dried Frond Tissues of Several Tree Fern Species from Peninsular Malaysia - Jamaludin, Azi Azeyanty; Bakar, Adibah Abu; Shahimi, Salwa; El-Banhawy, Ahmed; Ariffin, Muhammad Afiq Tajol; Pati, Siddhartha (CENTRAL ASIA AND THE CAUCASUS, 2022)
Extraction from field specimens of high-quality DNA often involves processing under liquid nitrogen that sometimes is not readily available in some laboratories. In this paper, a method of extracting DNA from silica-dried frond tissues of several tree fern species is described as existing protocols for genomic DNA isolation have their restrictions due to the existence of high content of tacky polysaccharides and polyphenols. Such protocols contaminate the DNA extracted with a viscous matrix, preventing for further use especially PCR performance. Polysaccharides and polyphenols were extracted in our adapted CTAB method before DNA precipitation and isopropanol was used to precipitate the genomic DNA. It was then amplified for testing with the non-coding primer trnL intron and trnL-F intergenic spacer. The highest concentration of DNA was from 0.03 g of frond tissues stored at -20 °C (205.80 ng/μL) for 24 hours, and even the lowest concentration obtained by this procedure was capable of generating enough PCR product for sequencing. The results showed the efficiency and reliability of the modified method as opposed to the unmodified method, suggesting that the combination of silica drying increases the quality and quantity of the DNA extracted.